The Form of Responsibility of Airlines as Business Entities For Unilateral Flight Cancellations Is Viewed From The Minister of Transportation Regulation Number 89 of 2015 Concerning Handling of Flight Delays In Scheduled Commercial Air Transport Business - Ismaidar Ismaidar; T. Riza Zarzani; Yossri Mantaw Sihombing (FKIP, Universitas Palangka Raya, 2024)
An airline is a company that provides services to goods and passengers traveling by air. The definition of aviation based on Law of the Republic of Indonesia Number 1 of 2009 concerning Aviation is a unified system consisting of the use of airspace, aircraft, airports, air transportation, flight navigation, safety and security, environment, supporting facilities and other public facilities. . Every flight activity is the responsibility of the airline company. Specifically responsible for errors in unilateral cancellation of passenger departures made by the airline. As a corporation or legal entity, airlines are obliged to provide compensation to passengers in accordance with the policies contained in aviation law and consumer protection law (UUPK). The research method used in this research is normative research which examines library materials sourced from secondary data, namely primary legal materials, secondary legal materials and tertiary legal materials. This legal material was obtained by taking a statutory approach and a conceptual approach. Then it is analyzed using qualitative methods to obtain a conclusion from the problem formulations that have been discussed. The purpose of this research is to find out the factors that cause departure cancellations by airlines and to find out how airlines are responsible for unilateral flight cancellations in terms of Regulation of the Minister of Transportation of the Republic of Indonesia Number 89 of 2015 concerning Handling Flight Delays in Scheduled Commercial Air Transport Business Entities in Indonesia.